2022
DOI: 10.3126/ajms.v13i7.43970
|View full text |Cite
|
Sign up to set email alerts
|

Role of hematological parameters and biochemical markers as a predictor of severity of COVID-19 patients

Abstract: Background: The etiological agent for pandemic COVID-19 is severe acute respiratory syndrome corona virus 2. Hematological and biochemical parameters are the indicators of inflammation and coagulopathy. Aims and Objectives: The present study aimed to determine how effectively the hematological parameters and biochemical markers can help predict the severity of critically ill COVID-19 patients. Materials and Methods: The current retrospective cohort study was conducted among 200 COVID-19 patients admitted in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Regarding the change in biochemical parameters of COVID-19 patients in this study, 83.1% of patients had CRP levels above the reference threshold, in which the death group had higher CRP concentrations than the discharged group (p<0.001). Some studies have shown that CRP levels are closely related to disease severity [22], but other research has concluded that CRP levels are not helpful for predicting the severity of COVID-19 [24]. The proportion of patients with ferritin concentrations over 1,000 ng/mL in the death group was higher than in the discharged group (77.9% vs. 36.2%; p<0.001).…”
Section: Evaluation Of Changes In Biochemical Parameters In Patients ...mentioning
confidence: 97%
“…Regarding the change in biochemical parameters of COVID-19 patients in this study, 83.1% of patients had CRP levels above the reference threshold, in which the death group had higher CRP concentrations than the discharged group (p<0.001). Some studies have shown that CRP levels are closely related to disease severity [22], but other research has concluded that CRP levels are not helpful for predicting the severity of COVID-19 [24]. The proportion of patients with ferritin concentrations over 1,000 ng/mL in the death group was higher than in the discharged group (77.9% vs. 36.2%; p<0.001).…”
Section: Evaluation Of Changes In Biochemical Parameters In Patients ...mentioning
confidence: 97%
“…The total platelet count at patient admission 201 (5-528) was increased to 228 (4-531) at discharge (p = 0.027), total leukocyte count (TLC) from 7 (3.4-33) to 9 (1.3-19) (p = 0.005), and absolute lymphocyte count (ALC) from 1 (0.07-301) to 2 (0.5-39) (p = 0.002). Hemoglobin (HB) level at patient admission 14 (4-12.5) was decreased to 13 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) at discharge (p = 0.002), absolute neutrophil count (ANC) from 9 (24-97) to 8 (1-95) (p = 0.004), absolute monocyte count (AMC) from 6 (1-208) to 5 (1-21) (p = 0.001), NLR from 14 (0.4-47) to 9 (0.01-43) (p = 0.001), and PLR from 27 (0.18-232) to 26 (0.94-101) (p = 0.044) (Table 2).…”
Section: Characteristics Of the Study Participantsmentioning
confidence: 99%
“…When compared to people with non-severe cases of COVID-19, patients with severe cases usually have lower leukocyte counts, smaller proportions of monocytes, eosinophils, and basophils, as well as higher NLR. 7 , 9 , 10 Although it is most useful for managing COVID-19 patients, especially in developing countries, not many studies have been done in Africa, primarily Ethiopia. More research is required to determine the appropriate NLR, MLR, and PLR values and their predictive value.…”
Section: Introductionmentioning
confidence: 99%